CHELATION THERAPY FOR IRON OVERLOAD: NURSING PRACTICE IMPLICATIONS - Eckes, Ellen J. (2011)
Many diseases of the blood are treated with blood transfusion therapy. Chronic transfusions can cause iron overload, and, if untreated, can cause end-organ damage. Chelation therapy provides a way of treating iron overload and minimizing its adverse effects. Nurses need to understand that iron overload is a consequence of chronic blood transfusion, and they need to know what effects it has on end-organs and what treatment options are available.